Document Digitization By Notary As Part of Cyber Notary Provision (Universitas Negeri Semarang, 2022)
The digital era is something that cannot be avoided in Indonesia and even throughout the world. Various Activities change from analog to digital. Digitization activities are carried out by a notary, one of the professionals, who digitize documents for needs, and orders of laws and regulations. This article aims to analyze the urgency of document digitization carried out by Notaries, and its implications for the performance of Notaries in the current era of technological transformation. In addition, this article will also discuss the obstacles and challenges for notaries in digitizing documents. This article is the result of research conducted using the socio-legal method. Socio-legal studies carry out textual studies of articles in legislation and policies that can be critically analyzed and explained their meanings and implications for legal subjects. Several laws and regulations require notaries to digitize, especially document digitization. The process of digitizing documents carried out by a Notary is still in the stage of digitizing printed documents and placing them in a file for uploading needs on the web or certain systems. This process has its obstacles and challenges for Notaries and employees who work at Notaries.